Rodinný dům - Bjaloňová, Natália (Vysoké učení technické v Brně. Fakulta stavební, 2025)
rodinný dom, novostavba, murovaná konštrukcia, projektová dokumentácia, sedlová stre-cha, plochá vegetačná strecha, keramické tvárnice, železobetónový strop, podkrovie, garáž, podpivničený, prevetrávaná fasáda

This bachelor thesis focuses on the design and development of project documentation for a new residential house. The building is designed as a basement structure with two above-ground floors. The project also includes a garage with a flat green roof. The main part of the house is covered by a gable roof with a wooden truss structure. The house is founded on plain concrete strip footings. The external walls of the basement are made of reinforced concrete, while the above-ground walls are constructed from ther-mally insulating ceramic blocks. Both load-bearing and non-load-bearing internal walls are made of ceramic blocks. The floor structure is designed as a monolithic reinforced concrete slab. The main entrance to the building is accessible from the adjacent road located on the nor-thern side of the plot. The plot has a slight slope. In the front part of the site, paved surfaces are designed, and a gravel drainage path is planned around the perimeter of the building.
Family House
Keywords: Bakalárska práca sa zaoberá návrhom a spracovaním projektovej dokumentácie pre novos-tavbu rodinného domu. Objekt je navrhnutý ako podpivničený s dvoma nadzemnými podla-žiami. Súčasťou stavby je aj garáž s plochou vegetačnou strechou. Zastrešenie hlavnej časti domu je riešené ako sedlová strecha s dreveným krovom. Dom je založený na základových pásoch z prostého betónu. Obvodové steny podzemného podlažia sú z vystuženého betónu a steny nadzemných podlaží sú z tepelnoizolačných kera-mických tvárnic. Vnútorne steny nosné aj nenosné sú z keramických tvárnic. Strop je riešený ako monolitická železobetónová doska. Hlavný vstup do budovy je z priľahlej komunikácie v severnej časti pozemku. Pozemok je mierne svažitý. V prednej časti objektu sú navrhnuté spevnené plochy a okolo objektu bude zriadený odkvapový chodník z kameniva.; family house; new-build; masonry structure; project documentation; gable roof; flat green roof; ceramic blocks; reinforced concrete slab; attic; garage; basement; ventilated facade